Evaluation of wound healing biomarkers of Interleukin 6 (IL-6), Vascular Endothelial Growth Factor (VEGF) and Matrix Metalloproteinases 9 (MMP-9) in post Lower Segment Caesarean Section (LSCS) patients consuming Channa Striatus extract - Omar, Julia; Shafii, Noorazliyana; Zainan, Ahmad Ezam; Kuttulebbai Naina Mohamed Salam, Sirajudeen (Ibn Sina Trust, 2020)
Background: Wound healing is a dynamic process which is divided into four phases; haemostasis, inflammatory, proliferation and tissue remodelling phases, that encompasses inflammatory cells, cytokines and growth factors. Interleukin-6 (IL-6), Vascular Endothelial Growth Factor (VEGF) and Matrix Metalloproteinase 9 (MMP-9) involve at the different phases of wound healing. Channa striatus (C.striatus) is a fresh water fish that is believed to have natural properties to promote wound healing. Currently, the effects of C.striatus on the cytokines and growth factors are not available.